VISUAL COMMUNICATION DESIGN STRATEGY FOR MUARADUA VILLAGE, SUKABUMI, AS AN EFFORT TO DEVELOP THE CREATIVE ECONOMY THROUGH A PARTICIPATORY ACTION RESEARCH APPROACH - Muhammad Fawwazianaufal Zidane; Riksa Belasunda; Ranti Rachmawanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to formulate a visual communication design strategy for Muaradua Village, Sukabumi, as an effort to develop a bamboo craft–based creative economy through a structured participatory approach. The method employed is Participatory Action Research (PAR), involving artisans, village youth, and local government officials actively across all stages of the research process, including problem identification, potential mapping, concept development, and media design. This approach was chosen based on preliminary findings indicating that the village’s main challenges lie not in the availability of bamboo raw materials or the artisans’ technical skills, but in weak collective management systems, limited coordination among local actors, and the absence of a shared village identity narrative. The research output, a village profile video, was developed through a collaborative process so that it functions not only as an external promotional medium but also as a tool for social reflection and a learning medium for the community. The findings indicate that community involvement in the creative process significantly increases a sense of ownership toward the resulting media, strengthens awareness of Muaradua Village’s identity as a bamboo village, and encourages the emergence of new initiatives in managing local potential. Conceptually, this study proposes a participatory-based village profile video design model as a visual communication design strategy that positions social processes as the primary foundation, so that development orientation is not limited to the quality of the final product but also emphasizes the social processes that support sustainability.